(untitled) (Journal of the College of Basic Education, 2022)
The contradictory binaries and the ways of dealing with them have differed throughout the historical developmentThe various fields of philosophy, art, architecture and design, and binaries in general and contradictoryAmong them, in particular, is one of the concepts that the constructivist intellectual orientations focused onAlthough a phenomenon gains its meaning by contrasting it with another phenomenon, the constructivist approach emphasizesThe need to organize the phenomena according to the encounters instead of paying attention to the collection of similaritiesThe result of interior design is the collection and reconciliation of elements, whether homogeneous or non-compliantHomogenous in a single composition that meets the individual’s aesthetic and functional requirements, the subject of dualities hasContacting the subject of interior design because it includes an infinite number of dichotomies from here it wasThe subject of the research, which included four chapters